(untitled) (International Journal of Physiology, 2019)
Background Hypertension is a significant global public health problem and it is associated with increased oxidative stress. Oxidative stress is disequilibrium between tissue oxidants (free radicals or reactive oxygen species ROS) and antioxidants and may be an integrative mechanism in the progress of cardiovascular diseases (CVD). Aims & Objectives To study the impact of dietary pattern on oxidative stress markers in newly diagnosed essential hypertension. Material and Method The study was conducted on 75 cases of essential hypertension (HT), 75 prehypertensives (preHT) and 50 control subjects for 15 months. After screening, serum uric acid (SUA) and serum malondialdehyde (S.MDA) level were investigated in both vegetarians (V) and nonvegetarians (NV) in all groups. Findings The difference in mean ± SD of SUA and S. MDA level between control, preHT and HT group were found to be highly significant (p<0.0001). SUA and S. MDA level was higher in NV as compared to vegetarians in all groups but significant results were found in case of SUA (p<0.001). Conclusion Long-term vegetarians have improved antioxidant status and coronary heart disease risk profile than do apparently healthy omnivores.